Disruption of evasive immune cell microenvironment in tumors reflects immunity induced by radiation therapy. (1st February 2016) - Filatenkov, Alexander; Baker, Jeanette; Strober, Samuel
ABSTRACT: Radiation administered to murine colon tumors induced durable remissions that were dependent on CD4 + and CD8 + T cell immunity, and antigen cross priming CD8 + dendritic cells (DCs). Remissions were associated with marked reductions in the infiltration of myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs) and Treg cells, and a marked increase in CD8 + T cells.